(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article analyzes the main scientific and practical methods for renovating industrial facilities for residential use, focusing on volumetric and spatial solutions. These methods are examined through classical and innovative approaches to address outdated infrastructure and spatial compositions that no longer meet contemporary ergonomic and functional standards. The study emphasizes adapting former industrial facilities to modern residential requirements while improving energy efficiency and environmental sustainability. Special attention is given to optimal transformation techniques that ensure effective renovation while enhancing urban quality. The integration of these renovated structures into the urban fabric supports sustainable development, considering socio-economic factors and preserving architectural heritage. A key aspect of these projects is resolving architectural deficiencies that characterize obsolete structures. The primary objective is to create a more harmonious environment by modernizing industrial facilities and incorporating new functions aligned with contemporary urban demands. Refunctionalization involves reconfiguring volumetric and spatial solutions and introducing modernized floor plans to improve compliance with living standards and increase functionality. This process maintains urban identity while addressing the growing demand for real estate in central and near-central areas. The principles of transformation preserving original structures, implementing strategic minimal interventions, and undertaking complete redevelopment where necessary are examined for their effectiveness in creating functional, energy-efficient, and aesthetically cohesive residential environments. Ultimately, the research highlights how applying these methods ensures the sustainable integration of renovated industrial facilities into modern urban landscapes. This allows them to retain historical significance while aligning with contemporary architectural, social, and environmental standards. The study confirms the importance of an interdisciplinary approach, combining architecture, urban planning, and sustainable design principles to optimize the use of former industrial spaces for residential purposes.